FULFILMENT EDUCATION RIGHTS OF BADUY COMMUNITY PERSPECTIVE POSITIVE LAW, CUSTOMARY, AND ISLAMIC - Bin Risal, Andi Asril; Ahmad, Ahmad (NOMOI Law Review, 2024)
The right to obtain access to education is clearly stated in the 1945 Constitution of the Republic of Indonesia (UUDNRI). However, it turns out that there are still Indonesian indigenous people who do not feel the right to education at all, they are the Baduy tribe. This research aims to explain and provide solutions so that the fulfillment of the right to education in Indonesia is equitable, especially for the Baduy community. This research compares the perspectives of positive law, customary law and Islamic law in understanding the right to education, and reveals the urgency of all three in determining priority actions for the Baduy tribe. Researchers used the Systematic Literature Review (SLR) method to collect data to find out and answer the problems in this research. The research results reveal that the right to education is part of Human Rights (HAM) which is very fundamental in nature. and Positive law is the highest rule in Indonesia which also guarantees the implementation of the right to education for all Indonesian people. The government must be firm and active in providing guarantees for the right to education in accordance with the mandate of the Constitution and several other state regulations, and play an important role in establishing positive law as the main guideline that must be obeyed and followed by all Indonesian citizens..